Executive functions in people with visual impairment - Beata Papuda-Dolińska (Lubelski Rocznik Pedagogiczny, 2020)
In the article the characteristics of executive functions in people with visual impairment is presented. Due to the empirically proven importance of executive functions for school learning, behavior regulation, organization of emotions and action, it is legitimized to find their specific role in mechanisms compensating for the lack of sight and behaviors based on non-visual techniques. The development and operation of individual executive functions in blind people is also characterized by specificities mentioned in the article. The characteristics were made taking into account variables that differentiate the quality of executive functions in the population of people with visual disabilities: the degree of visual impairment, age, the time of disability acquisition, the method of diagnosis. Based on current literature, the impact of haptic-auditory experience, possible delays in the cognitive development, owning of visual images in people with visual impairment on specific executive functions have been analyzed.